Heritage Encounters: Critical Place-Based Learning and the Making of Historical Awareness - Tesalonika Kristina Cendani; Romadi Romadi (Indonesian Journal of History Education, 2025)
This qualitative study examines how direct engagement with local heritage sites shapes historical consciousness in post-colonial classrooms. Engaging Indonesian tenth-graders with Liyangan, a pre-colonial site buried by volcanic eruption, the research investigates site visits as critical pedagogical intervention against textbook-dominated history instruction. Drawing on interviews with teachers, students, and site custodians, findings reveal that heritage encounters foster multidimensional awareness: students demonstrated heightened curiosity about marginalized local pasts, stronger preservation motivation, and deeper engagement with cultural traditions. The model creates transformative spaces where formal knowledge meets community memory, enabling learners to confront buried histories as reconciliatory practice. While implementation faces structural constraints—time, finance, transportation—this study contributes to global conversations on place-based pedagogy and heritage education in post-colonial societies.